1999
DOI: 10.1002/(sici)1097-4547(19990701)57:1<48::aid-jnr6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

2-deoxy-d-glucose protects hippocampal neurons against excitotoxic and oxidative injury: Evidence for the involvement of stress proteins

Abstract: Food restriction can extend life span in rodents and was recently reported to increase the resistance of neurons in the brain to excitotoxic and metabolic insults. In principle, administration to ad libitum fed rodents of an agent that reduces glucose availability to cells should mimick certain aspects of food restriction. We now report that administration of 2-deoxy-D-glucose (2DG), a non-metabolizable analog of glucose, to adult rats results in a highly significant reduction in seizure-induced spatial memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…GRP78 binds Ca 2+ , folds damaged proteins (Bole et al, 1986;Lee, 1987), and has been found to inhibit oxyradical accumulation (Liu et al, 1998;Yu et al, 1999;Lee et al, 1999). In cultured rat hippocampal neurons, it has been reported that pretreatment with 2-deoxy-d-glucose, an inducer of GRP78 expression, inhibited cell death and reactive oxygen species accumulation, and stabilized mitochondrial transmembrane potential after cells have been challenged by glutamate and oxidant FeSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 binds Ca 2+ , folds damaged proteins (Bole et al, 1986;Lee, 1987), and has been found to inhibit oxyradical accumulation (Liu et al, 1998;Yu et al, 1999;Lee et al, 1999). In cultured rat hippocampal neurons, it has been reported that pretreatment with 2-deoxy-d-glucose, an inducer of GRP78 expression, inhibited cell death and reactive oxygen species accumulation, and stabilized mitochondrial transmembrane potential after cells have been challenged by glutamate and oxidant FeSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Associated with the neuroprotective effect of IF was increased levels of the stress resistance proteins and brain-derived neurotrophic factor ( BDNF) [41,42]. Interestingly, administration of 2-deoxy-d-glucose (2DG; a nonmetabolizable glucose analog) to rats, which mimics some aspects of CR, also increases the production of stress resistance proteins in brain cells [43]. The latter findings suggested the possibility that IF would increase the resistance of neurons to a stroke because data from other studies have shown that protein chaperones and BDNF can reduce ischemic brain damage [43][44][45][46].…”
Section: If Protects Neurons and Cardiac Myocytes Against Ischemic Inmentioning
confidence: 99%
“…Interestingly, administration of 2-deoxy-d-glucose (2DG; a nonmetabolizable glucose analog) to rats, which mimics some aspects of CR, also increases the production of stress resistance proteins in brain cells [43]. The latter findings suggested the possibility that IF would increase the resistance of neurons to a stroke because data from other studies have shown that protein chaperones and BDNF can reduce ischemic brain damage [43][44][45][46]. We therefore subjected rats that had been maintained for 3 months on either an IF or a control diet to transient middle cerebral artery occlusion, a model of ischemic stroke [41].…”
Section: If Protects Neurons and Cardiac Myocytes Against Ischemic Inmentioning
confidence: 99%
See 1 more Smart Citation
“…When rodents were administered with 2-DG for 2 weeks, neurons in their brains exhibited an increased resistance to dysfunction and death in experimental models relevant to the pathogenesis of AD, PD, and stroke [88,89,122]. More interestingly, the mechanism whereby 2-DG supplementation protects neurons may be similar to that of CR because levels of some stress-induced proteins, heat shock protein 70 and glucose-regulated protein 78, are increased in neurons of rats and mice given 2-DG [88,89,122]. Although prolonged treatment of 2-DG has shown similar neuronal protection to that produced by CR, few studies has been performed in order to determinate nociception.…”
Section: Future Direction: Toward a Chemical Cr Mimeticmentioning
confidence: 99%